Paraguay : 2009 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Paraguay. (IMF Staff Country Reports; Country Report ;, 2009)
This 2009 Article IV Consultation highlights that the Paraguayan economy performed very well over the past five years, with real GDP growth averaging about 5 percent a year-the best in a generation. The fiscal position strengthened considerably, thereby reducing public debt sharply to relatively low levels. The economy grew by nearly 6 percent in 2008, but growth decelerated in the last quarter of the year. Paraguay's macroeconomic outlook has also been negatively affected by the deterioration in the global environment.